Assessment and management of dysphagia in the neonatal intensive care units in India: A survey report - Mary Jose; Rahul Krishnamurthy; Lakshmi Venkatesh; Nutan Kamath; Kamalakshi G. Bhat; Radish Kumar Balasubramanium (Elsevier, 2024)
Background: Evidence-based assessment and management of dysphagia in neonates, especially those in the neonatal intensive care unit (NICU), are limited. Understanding existing clinical practices may be the first step toward developing a consensus. The current study aimed to identify clinical practice patterns of speech-language pathologists (SLPs) in India towards facilitating the development of feeding skills and assessment and management of dysphagia among neonates. Method: An electronic survey questionnaire comprising 46 questions categorized into two main sections (demographics and a hypothetical case scenario) was emailed to 35 SLPs practicing in the NICU. The hypothetical clinical case was created to include considerations of assessment and management of dysphagia in the NICU, and the participants answered questions about clinical decision-making. Results: As many as 22 individuals completed the survey. The responses were analyzed descriptively to identify themes and trends in practice patterns. Our results revealed varied practice patterns in the clinical swallowing assessment and management approaches for neonatal dysphagia. Conclusion: There is a need to develop a consensus statement and standard guidelines for the assessment and intervention for dysphagia by the SLP in the NICU. Translation of current evidence-based research into clinical practice is critical to patient care.